Development as Leadership-led Change : A Report for the Global Leadership Initiative - Andrews, Matt (World Bank, 2012)
Much of the work on reform and development has focused on the identification and diagnosis of problems and on the formulation of technically sound measures to address these problems. But the main challenge that often confronts policy makers in attempting to undertake reforms is not in the 'what', what is the problem and what are the remedies for it, but in the 'why', why does the problem persist, which some research has begun to address, and, more critically, in the 'how' given the why, how to manage the often complex process of change that accompanies any attempt at reform. It is in the latter where the rubber hits the road. Development involves change. But many development initiatives produce unimpressive levels of change in the countries, organizations, and outcomes they target and are disappointing in the final results. This is the case in social sector initiatives, core public management reforms, and even macroeconomic adjustment operations. Change is often limited even when countries adopt solutions in their forms, in apparently good faith and on time (or in reasonable time). This research paper aims to (modestly) contribute to such research by exploring what it takes to get change done; and particularly what role leadership plays in effecting change.